Neural Differences between Covert and Overt Attention Studied using EEG with Simultaneous Remote Eye Tracking - Kulke, Louisa V.; Atkinson, Janette; Braddick, Oliver (Frontiers in Human Neuroscience, 2016)
Research on neural mechanisms of attention has generally instructed subjects to direct attention covertly while maintaining fixed gaze. This study combined simultaneous eye tracking and EEG to measure neural attention responses during exogenous cueing in overt attention shifts (with saccadic eye movements to a target) and compared these with covert attention shifts (responding manually while maintaining central fixation). EEG analysis of the period preceding the saccade latency showed similar occipital response amplitudes for overt and covert shifts, although response latencies differed. However, a frontal positivity was greater during covert attention shifts, possibly reflecting saccade inhibition to maintain fixation. The results show that combined EEG and eye tracking can be successfully used to study natural overt shifts of attention (applicable to non-verbal infants) and that requiring inhibition of saccades can lead to additional frontal responses. Such data can be used to refine current neural models of attention that have been mainly based on covert shifts.